Multicolor multicycle molecular profiling (M3P) with quantum dots for single-cell analysis - Zrazhevskiy, Pavel (2013)
Here we present a detailed protocol for molecular profiling of individual cultured mammalian cells using multicolor multicycle immunofluorescence with quantum dot probes. It includes instructions for cell culture growth and processing (2 h + 48–72 h for cell growth), preparation and characterization of universal quantum dot probes (4.5 h + overnight incubation), cyclic cell staining (~4.5 h per cycle), and image analysis (varies by application). Use of quantum dot fluorescent probes enables highly multiplexed, robust quantitative molecular imaging with a conventional fluorescence microscopy setup, whereas the probe preparation methodology employing self-assembly between Protein A-decorated universal quantum dots and intact primary antibodies offers fast, simple, and purification-free route for on-demand preparation of antibody-functionalized quantum dot libraries. As a result, this protocol can be employed by biomedical researchers for a variety of cell staining applications and, with further optimization, for staining of other biological specimens (e.g., clinical tissue sections).